Three-dimensional ultrasonic wave simulation in laminated CFRP using elastic parameters determined from wavefield data. (1st November 2019) - Nakahata, K.; Amano, Y.; Ogi, K.; Mizukami, K.; Saitoh, T.
Abstract: A numerical modeling of ultrasonic testing (UT) for a carbon fiber reinforced plastic (CFRP) material is presented. Due to the heterogeneity caused by the several unidirectional lamina stacked at different angle, the CFRP shows unique mechanical properties and leads to ultrasonic wave skewing and scattering. In this paper, we present a large-scale finite element (FE) simulation based on the image-based modeling approach. We model the mesoscopic heterogeneity of the CFRP in the numerical discretization by using the voxel of the same size. The determination of the anisotropic elastic stiffness of each lamina is essential to the FE simulation. Here, we estimated the parameters via an inversion method using wavefield visualization data. The parameters were fed into the 3D wave propagation simulations in the laminated CFRPs. The simulation and experimental results showed good agreement with respect to the wave velocity and the spread of the ultrasonic waves. It was found that the mesoscopic modeling and parameterization of the elastic stiffness of the lamina were important for the UT simulation. Graphical abstract: